Mucosa-associated lymphoid tissue (MALT) lymphoma of the stomach: features of pathomorphological diagnostics - V. A. Tumanskiy; V A. Shavrin (Patologìâ)
On the base of our own observations and literature data it was determined that the distinctive pathologic features of MALT-lymphoma of the stomach are the presence of a dense diffuse lymphocytic infiltrate of centrocyte-like tumor cells of marginal zone (small cells resembling centrocytes with distinct bright rim of cytoplasm, with small nuclei of irregular shape, sometimes – split, containing coarse chromatin and indistinct nucleoli) in the lamina propria between the reactive lymph follicles and glands of the mucous membrane, monocytoid B-lymphocytes characterized by clear cell borders, broad light cytoplasm and bean-like nucleus, plasma cells, which may contain Dutcher bodies – intranuclear inclusions of immunoglobulins; single large centroblast-like or immunoblast-like cells having round-oval or slightly irregular in shape nuclei with 1-3 nucleoli, or vesicular-like round in shape nuclei with compact, centrally located nucleolus; small lymphocytes. Infiltration looks as tumorcell layers or, more rarely, fuzzy nodular cellular formations. An important diagnostic criterion is the presence of "lymphoepithelial lesions" zones of glands due to infiltration by 3 or more centrocyte-like tumor cell aggregates with glands’ basement membranes destruction. In the damaged glands epithelium edema and eosinophilia are marked, but if extensive infiltration is present among the lymphoid infiltrate there are only clusters of degenerated cells at the site of destroyed epithelium. Low-grade MALT-lymphoma is characterized by the absence of distinct macroscopic changes and the prevalence of "mature" tumor cells over the blasts in histological picture. MALT-lymphoma with signs of transformation into high-grade lymphoma is characterized macroscopically by distinct exophytic component, hyperplasia of folds with ulcerous defects up to 1-2 cm in diameter. Histologic picture displays a significant amount of blast cells – both in the infiltrate and in the areas of "lymphoepithelial lesions". There are usually less reactive follicles than in low-grade lymphoma. High-grade MALT-lymphoma is macroscopically characterized by predominantly infiltrative-ulcerative lesions of stomach and gastric ulcer defects up to 4-5 cm in diameter. Histologically there is a significant number of atypical centroblast-like and immunoblast-like cells (sometimes polynuclear), numerous figures of mitosis and apoptotic bodies are found.